2019
DOI: 10.1038/s41598-019-43877-1
|View full text |Cite
|
Sign up to set email alerts
|

The significance of serum HMGB1 level in humans with acute paraquat poisoning

Abstract: High-mobility group box 1 (HMGB1) mediates acute lung injury in a mouse model of paraquat poisoning. However, published reports showing a clinically relevant association between HMGB1 and paraquat exposure are lacking. The objective of the present study was to investigate the potential role of serum HMGB1 level as a prognostic marker of mortality in patients with paraquat poisoning in a clinical setting. This retrospective observational cohort study included a convenience sample of 92 patients with acute paraq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Paraquat induces oxidative damage and cell death by generation of reactive oxygen species (ROS) including hydrogen peroxide, superoxide anion, and hydroxyl radicals (Fan et al, 2018;Chen et al, 2019a), and induction of cellular apoptosis (Kong et al, 2019). PQ toxicity is related to its capacity to capture electrons in cellular redox reactions and inhibit the reduction of NADP + to NADPH in the cytosolic fraction, which induce oxidative stress by the overproduction of superoxide anion (O 2− ) (Baltazar et al, 2014;Blanco-Ayala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraquat induces oxidative damage and cell death by generation of reactive oxygen species (ROS) including hydrogen peroxide, superoxide anion, and hydroxyl radicals (Fan et al, 2018;Chen et al, 2019a), and induction of cellular apoptosis (Kong et al, 2019). PQ toxicity is related to its capacity to capture electrons in cellular redox reactions and inhibit the reduction of NADP + to NADPH in the cytosolic fraction, which induce oxidative stress by the overproduction of superoxide anion (O 2− ) (Baltazar et al, 2014;Blanco-Ayala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gas chromatography-time-of-flight mass spectrometry (GC-TOF/MS) is one of the most widely used platforms in non-targeted metabolomics studies (Lenz and Wilson, 2007), which provides high chromatographic resolution, high mass measurement accuracy, and rapid spectrum acquisition (Ni et al, 2016). Given the poor prognosis of PQ intoxication, previous studies focused on mining potential prognosis biomarkers from patient samples by either metabolomics or other non-highthroughput approaches (Yeo et al, 2012;Wunnapuk et al, 2013;Wan et al, 2018;Chen et al, 2019a). Relatively few studies paid attention to the metabolic feature caused by PQ exposure to help us investigate the underlying mechanisms, which might contribute to develop new therapeutic targets and diagnosis biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…However, notably, patients are still likely to face death even at low plasma paraquat concentrations 9 . More recently, some biochemical indicators have been reported to potentially guide the prognosis of paraquat poisoning, including pancreatic enzymes, high‐mobility group box 1 (HMGB1), serum creatinine, serum uric acid and others 13‐16 . Although these biochemical indicators can somehow reflect the damage degree of corresponding organs, the hysteresis phenomena and the fact that multiple organs were not taken into account have limited the reliability and prognostic values of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2019;Shao et al, 2019). PQ is extremely toxic to humans (Xu et al, 2017;Chen F. et al, 2019). Studies have shown that when ingesting about 10 ml PQ, patients can die of multiple organ failure a few hours later (Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%